2011
DOI: 10.1093/nar/gkr950
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure and DNA-binding properties of the phosphoesterase domain of DNA ligase D

Abstract: The phosphoesterase (PE) domain of the bacterial DNA repair enzyme LigD possesses distinctive manganese-dependent 3′-phosphomonoesterase and 3′-phosphodiesterase activities. PE exemplifies a new family of DNA end-healing enzymes found in all phylogenetic domains. Here, we determined the structure of the PE domain of Pseudomonas aeruginosa LigD (PaePE) using solution NMR methodology. PaePE has a disordered N-terminus and a well-folded core that differs in instructive ways from the crystal structure of a PaePE•M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The architecture of the structures implies that the surface loop is flexible and may enclose the DNA once the proper substrate is engaged for catalysis (Supplementary Figure S1E,1F). This speculation is supported by NMR solution studies that suggest that the crystal structures represents a ‘closed’ active site formation, and that the loop moves away from the active site in the absence of a substrate ( 33 ). This study also showed that upon addition of substrate, spectral perturbations were observed that indicated movement of the loop region, and formation of a ‘closed’ active site from an ‘open’ one.…”
Section: Resultsmentioning
confidence: 90%
“…The architecture of the structures implies that the surface loop is flexible and may enclose the DNA once the proper substrate is engaged for catalysis (Supplementary Figure S1E,1F). This speculation is supported by NMR solution studies that suggest that the crystal structures represents a ‘closed’ active site formation, and that the loop moves away from the active site in the absence of a substrate ( 33 ). This study also showed that upon addition of substrate, spectral perturbations were observed that indicated movement of the loop region, and formation of a ‘closed’ active site from an ‘open’ one.…”
Section: Resultsmentioning
confidence: 90%
“…32 More recently, backbone flexibility in DNA ligase D was suggested to be involved in both activation and inhibition of this enzyme. 33 …”
Section: Discussionmentioning
confidence: 99%
“…In each titration case, assignments were carefully transferred from the CD3 free TROSY spectra to saturated TROSY spectra. The scaled chemical shift, δppm = ((Δ 1 H) 2 +0.11(Δ 15 N) 2 ) 0.5 (Natarajan et al, 2012). The residues that showed spectral changes were identified if (a) they showed scaled chemical shift changes greater than 1σ above the 25% trimmed mean deviation when comparing in the presence and absence of saturated amounts of CD3 state, and (b) lesser than 1σ below the 25% trimmed mean deviation in the ratio of NMR signal intensity between CD3 saturated-state and CD3 free state (Figure 2).…”
Section: Methodsmentioning
confidence: 99%